Accounting Systems (Book). - Cannon, Arthur M.; Johnson, Arnold W. (The Accounting Review, 1954)
Reviews the book "Accounting Systems–Design and Installation," 2nd ed., by J. Brooks Heckert and Harry D. Kerrigan.